The Analysis of Relationship Between Quality of Graduates and Education Financing Management in Private Islamic School - Enny Diah Astuti; Hendy Tannady; Arkam Lahiya; Dasep Supriatna; Eka Selvi Handayani (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of education financing management on the quality of graduates in a private Islamic school in Banten. In this study, there are two variables involved, namely the Education Funding Management variable which is positioned as the independent variable or independent variable and is symbolized by the variable (X). This variable is a variable that is considered to influence or cause the dependent variable or dependent variable to arise. Meanwhile, what is positioned as the dependent variable or the dependent variable in this study is the Quality of Graduates. The dependent variable or dependent variable is considered the variable that is affected or becomes the result because of the existence of the independent variable and is symbolized by (Y). This research uses quantitative research methods. Based on the results of the research and discussion that has been described previously, it can be put forward a number of findings as follows: education financing management is in the moderate category. This means, the implementation of education financing management is not all good and in terms of education funding budget allocations are managed and implemented effectively. The quality of graduates is in the moderate category, this means that schools have not been able to produce good quality graduates. Only 18% of graduates each year are able to enter public schools.